Art and Religious Revitalization Movements in (Post)Communist Romania: The Zidarus' 'Case'. (3rd April 2017) - Asavei, Maria-Alina
ABSTRACT: Little attention has been given in academic analyses of religious revitalization movements to the relationship between artistic production and cultural religious revivals. This paper aims to address this lacuna by exploring the purpose(s) and meaning(s) of artistic production in (post)-communist Romania's unofficial religious revitalization movements. Marian and Victoria Zidaru's controversial body of spiritual art and their 'cultic milieu' are employed as a case study. In the cultural sections of the Romanian press, the Zidarus' contested art production has either been interpreted through the lens of 'offensive nationalism' and 'protochronist nationalism' or reduced to 'primitive traditionalism' and 'cultural Rasputinism'. Against these views, the argument this paper puts forth is that the Zidarus' artistic production refashions the meanings of 'religion', being occasioned by a peculiar 'artistic prophetic activism' (as theorized by Tom Block) instantiated by a personal effort to overcome the long and disorienting transition from communism to liberal democracy, and to offer a paradigm for the socially empowering artist who—like the ancient and mediaeval prophet—struggles to provide contemporary spiritual amelioration. The Zidarus' body of prophetic art from 1985 to 2014 remains faithful to the idea that art can trigger a spiritual revolution with palliative effects.